Placement of long-acting reversible contraception for minors who are mothers should not require parental consent - Kaszubinski, Savannah (Journal of medical ethics, 2022)
Decreasing unintended teenage pregnancy, especially repeat teenage pregnancy, is an important public health goal. Unfortunately, legal barriers in the USA impede this goal as all minors are unable to consent for birth control in 24 states, and only 10 of those states allow consent after the minor has given birth according to state statutory law. Placement of long-acting reversible contraception (LARC) is one of the most effective methods of preventing rapid repeat pregnancies. However, restrictions are placed on adolescents who may not have the option of parental consent if the parents are unwilling, or not present, to give consent. A predicament arises when healthcare professionals are willing to place the contraceptive for the patient, but cannot due to the restrictions and guidelines outlined by each state. Even though these adolescents are legally viewed as minors, adolescent mothers should be able to consent to the placement of LARC. Notably, adolescents have the legal ability to give consent for the healthcare of their child starting in the prenatal period. I argue that this ability should be extended to include adolescent consent for their own healthcare. Additionally, the procedure to place LARC is relatively low risk and highly effective, which is an opportune situation to allow minors to consent. Allowing adolescents to consent to LARC after delivery is a simple and effective way to decrease rapid repeat pregnancy rates in the USA.